(untitled) (Surya Abdimas, 2024)
Reflective journal writing is a type of writing that contain description of actual events by incorporating reflective components and providing context for an event that encompasses feelings and distinct personal circumstances. Writing a reflective journal essay is one of the outcomes of the community service program for students, especially at IAIN Langsa. In practice, some students found writing reflective essays challenging. To offer assistance in producing these kinds of articles through a mentorship program is considerably needed. Asset-Based Community Development (ABCD) is the approach employed in this project, which looks at the potential within the community—in this case, the higher education institution. A total of six sessions mentorship program were held from December 13th to December 29th, 2024. 30 students from Tarbiyah and the Teacher Training Faculty of IAIN Langsa participated in the program. The activity involved coaching by integrating theory, practice, and feedback. The result demonstrated that the participants can identify structure and elements of reflective writing and they can determine writing angels and elaborate them in their writing. The program also creates an interactive learning environment where the participants can discuss and share knowledge as well as work collaboratively. Additionally, by giving students feedback throughout the program, it fosters their learning autonomy and enhances their writing abilities. Above all, they are able to complete the tasks on schedule.